Investigation of the 2015 Ms5.8 Alxa Left Banner earthquake sequence: Aftershock evolution and seismogenic structure - Zeng, Xianwei; Li, Xinyan; Li, Mengya; Li, Wenjun (Frontiers in Earth Science, 2023)
The 2015 Ms5.8 Alxa Left Banner earthquake (Alxa Ms 5.8 eathquake) struck a sparsely inhabited area of Inner Mongolia, northwestern China. However, as first > Ms 5 event on the Ningxia–Inner Mongolia segment of the North–South seismic zone for 24 years, the earthquake is of considerable scientific interest. In this study, the seismic distribution of the Alxa Ms 5.8 earthquake sequence was redetermined via the analysis of data from permanent and campaign seismic stations using the double-difference (DD) method. To improve the completeness of the earthquake catalog, the match and locate (M&L) method was then used to detect micro-earthquakes. The mainshock rupture started at the eastern end of the fault, propagating east-to-west and deep-to-shallow. Aftershocks were distributed in a NEE trending (N70–75E), with a 12-km length and a dominant depth of 15–25 km. Moreover, the aftershocks formed two distinct segments (the eastern and western segments). The mainshock and early aftershocks were primarily located on the eastern segment and relatively fewer aftershocks occurred on the western segment. Subsequently, from March to June 2016, three earthquakes of > ML3.0 occurred in the seismic gap between the eastern and western segments, releasing stress that was not released by the mainshock. According to the aftershock evolution, the seismogenic fault of Alxa Ms 5.8 eathquake associated with a NEE-striking blind fault that becomes steeply dipping toward the south. Furthermore, the seismogenic fault is a western branch fault of the Dengkou–Benjing blind fault (DBF). The aftershock evolution and inferred seismogenic structure provide a reference for further research in the study area.